Waste rock characterisation and stability assessments for feasibility level studies - Dwumfour, D; Dixon, J; Mylvaganam, J (Slope Stability 2020: 2020 International Symposium on Slope Stability in Open Pit Mining and Civil Engineering, 2020)
Regulatory approval frameworks, such as that of the Department of Mines, Industry, Regulation and Safety (DMIRS) in Western Australia Mining Proposal approval process, require detailed design reports for waste rock dumps for mining projects. Determination of waste rock shear strength parameters for waste rock dump design at a feasibility project level is often challenging as a result of factors such as spatial variation, lack of representative data and limited knowledge of waste rock movement schedules. Trial open pits or blasted representative material are rarely available. A practical approach to derive design material parameters using the Barton–Kjaernsli criterion (Barton & Kjaernsli 1981; Barton 2008) is provided, based on available site-specific feasibility level geotechnical data for a case study site in the Pilbara region of Western Australia. Stability assessments for various scenarios including for possible unfavourable conditions such as earthquake and storm events expected in the long-term are required to demonstrate that safe operational conditions and effective mine closure designs can be facilitated.
Keywords: material classification; waste rock dumps; slope stability analysis